A low-temperature silver paste for easy-to-weld solar cells and a preparation method thereof

By combining modified dendritic and nanospherical silver powders, the welding pull of low-temperature silver paste was improved, solving the problem of insufficient welding strength in HIT batteries and extending the service life of battery modules.

CN115579171BActive Publication Date: 2025-01-07CHANGSHA ADVANCED MATERIALS IND RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211289558.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2025-01-07
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

The existing low-temperature silver paste for HIT batteries has insufficient welding pull, which makes the solder strips easy to fall off and affects the life of the battery module.

Method used

Modified dendritic silver powder and modified nanosphere silver powder are used, modified with glycerol, and combined with specific proportions of resin, organic solvent, curing agent, dispersant and adhesion promoter to prepare an easy-to-weld low-temperature silver paste, which improves the dispersibility and bonding strength of silver powder and forms a better curing effect.

Benefits of technology

The welding pull force of the low-temperature silver paste was increased to over 1.2N, which significantly improved the welding strength and service life of HIT batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003900817940000041
    Figure BDA0003900817940000041
  • Figure BDA0003900817940000071
    Figure BDA0003900817940000071
  • Figure BDA0003900817940000081
    Figure BDA0003900817940000081
Patent Text Reader

Abstract

The present invention relates to a low-temperature silver paste for easy-to-weld solar cells and a preparation method thereof. The low-temperature silver paste for easy-to-weld solar cells comprises the following components: 85%-92% silver powder, 3%-8% resin, 3%-8% organic solvent, 0.2%-1.5% curing agent, 0.2%-1% dispersant, and 0.5%-2% adhesion promoter; the dendritic silver powder and nano-spherical silver powder added in the present invention are modified by polypropylene glycol, and a mixed solution of polypropylene glycol and ethanol is added to the silver powder. The polypropylene glycol is used as a surface coating agent of the silver powder to form a coating, which effectively prevents the silver powder from agglomerating and improves the bonding strength, making the silver powder easier to disperse and evenly distributed, and improving the wettability of the silver powder. At the same time, the surface hydroxyl groups formed on the surface of the silver powder participate in the curing reaction with the epoxy groups in the organic carrier to form a better curing effect, effectively improving the welding tensile force of the slurry, and the welding tensile force can reach more than 1.2N, which is much higher than ordinary low-temperature silver paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cell silver paste preparation, and in particular relates to an easy-to-weld low-temperature silver paste for solar cells and a preparation method thereof. Background Art

[0002] HIT (silicon heterojunction solar cell) was first successfully developed by Japan's Sanyo Company. Since then, research institutions around the world have significantly increased their research on heterojunction solar cells. HIT cells are formed by amorphous silicon and crystalline silicon materials. Amorphous silicon thin films are deposited on crystalline silicon. It combines the advantages of crystalline silicon cells and thin-film cells and is one of the important development directions of high-conversion efficiency silicon-based solar cells. HIT cells combine the ultra-low temperature production and manufacturing advantages of thin-film solar cells, avoiding traditional high-temperature processes. The temperature requirement is only 200°C, and both sides can generate electricity. The core competitiveness of power generation is obvious.

[0003] The function of silver paste is to collect the current generated by solar cells, lead it out through welding strips and finally enter the power grid or the end of use. Traditional silver paste crystalline silicon cells are sintered at high temperature, and the silver powder and glass powder melt and etch the silicon plate to form a reliable bond and ohmic contact with the silicon wafer. For HIT cells, since high temperature will destroy the hydrogenated amorphous silicon in the HIT cell and reduce the cell conversion efficiency, low-temperature curing solar cell silver paste is required. Different from the good welding tensile force of high-temperature silver paste that melts and etches the silicon plate, low-temperature silver paste is bonded to the silicon wafer through organic resin, and the tensile force is often less than 1N, which causes the welding strip to fall off. Therefore, it is necessary to develop a HIT low-temperature curing solar cell silver paste with high welding tensile force. Summary of the invention

[0004] In order to solve the problem of low welding tension of conventional low-temperature silver paste for HIT cells, the present invention aims to provide an easy-to-weld low-temperature conductive silver paste for solar cells and a preparation method thereof, which can effectively improve the life of HIT cell components.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a low-temperature silver paste for easy-to-weld solar cells, comprising the following components:

[0006] Silver powder 85%-92%,

[0007] Resin 3%-8%,

[0008] Organic solvent 3%-8%,

[0009] Curing agent 0.2%-1.5%,

[0010] Dispersant 0.2%-1%,

[0011] Adhesion promoter 0.5%-2%;

[0012] The silver powder is a mixture of modified dendritic silver powder and modified nano-spherical silver powder, wherein the mass ratio of the modified dendritic silver powder to the modified nano-spherical silver powder is (2-16):1;

[0013] The modified dendritic silver powder is polyglycerol modified dendritic silver powder, and the modified nano spherical silver powder is polyglycerol modified nano spherical silver powder. Further, the modified dendritic silver powder has a particle size distribution D50 of 2.0-5.0 μm and a tap density of 4-7 g / mL.

[0014] Furthermore, the modified nano-spherical silver powder has a particle size distribution D50 of 100-500 nm and a tap density of 3-8 g / mL.

[0015] Furthermore, the resin includes a main resin and an auxiliary resin, the main resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and acrylic modified epoxy resin, and the auxiliary resin includes one or more of polyester resin, polyurethane resin, and acrylic resin.

[0016] Furthermore, the organic solvent includes one or more of dibasic acid ester (DBE), diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and dimethyl adipate.

[0017] Furthermore, the curing agent includes one or more of isocyanate, imidazole, and modified amine.

[0018] Furthermore, the dispersant includes one or more of polyester and polyurethane, and the adhesion promoter includes a silane coupling agent.

[0019] Furthermore, the modified dendritic silver powder and modified nano-spherical silver powder are prepared by the following method: the dendritic silver powder and the nano-spherical silver powder are respectively added to a mixed solution of excess (2-5 times the mass of the silver powder) polypropylene glycol and ethanol, the mass ratio of polypropylene glycol to ethanol is controlled to be equal to 3: (1-9), the stirring speed is set to 100-200 r / min, stirring is carried out for 3-7 hours, filtering and drying, and the modified dendritic silver powder and modified nano-spherical silver powder are respectively obtained.

[0020] The present invention also provides a method for preparing the above-mentioned easy-to-weld solar cell low-temperature silver paste, comprising the following steps:

[0021] S1, adding dendritic silver powder to a mixed solution of polypropylene glycol and ethanol, stirring, filtering and drying to obtain modified dendritic silver powder; adding nano-spherical silver powder to a mixed solution of polypropylene glycol and ethanol, stirring, filtering and drying to obtain modified nano-spherical silver powder;

[0022] S2, taking a resin, an organic solvent, a dispersant, and an adhesion promoter, mixing them, putting them into a centrifugal disperser for dispersion, and obtaining a mixed carrier A;

[0023] S3, mixing the mixed carrier A with the curing agent, stirring at a low speed to obtain a mixed carrier B;

[0024] S4, adding modified dendritic silver powder and nano silver powder to the mixed carrier B in batches, stirring while adding, the stirring speed is 100-200r / min, to obtain a preliminarily dispersed slurry;

[0025] S5, rolling the preliminarily dispersed slurry for multiple times to obtain a low-temperature silver paste for solar cells that is easy to weld.

[0026] Further, the step S2 specifically includes the following operations: adding the main resin in the resin to the solvent, stirring at a constant temperature of 60-80°C in a water bath at a stirring speed of 300-500r / min, until the main resin is completely dissolved, filtering impurities to obtain a low-viscosity resin carrier; taking the low-viscosity resin carrier, the remaining auxiliary resin in the resin, the organic solvent, the dispersant, and the adhesion promoter, mixing, and putting into a centrifugal disperser for dispersion at a speed of 800-1000r / min for 1-3min to obtain a mixed carrier A;

[0027] In the steps S4 and S5, the temperature is controlled to be less than 20° C. during stirring.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The dendritic silver powder and nano-spherical silver powder added in the present invention are modified by polypropylene glycol. A mixed solution of polypropylene glycol and ethanol is added to the silver powder. Polypropylene glycol is used as a surface coating agent of the silver powder to form a coating, which effectively prevents the silver powder from agglomerating and improves the bonding strength, making the silver powder easier to disperse and evenly distributed, thereby improving the wettability of the silver powder. At the same time, the surface hydroxyl groups formed on the surface of the silver powder participate in the curing reaction with the epoxy groups in the organic carrier, thereby forming a better curing effect and effectively improving the welding tensile force of the slurry.

[0030] (2) The combination of dendritic silver powder and nano-spherical powder can make the silver powder in the slurry better overlap. During the drying process of the slurry, the nano-spherical powder melts and connects the dendritic silver powder and the ITO film, so that the slurry has stronger welding tensile force after drying.

[0031] The present invention improves the tensile force of the low-temperature silver paste from the above two aspects, so that the welding tensile force can reach more than 1.2N, which is much higher than that of ordinary low-temperature silver paste. DETAILED DESCRIPTION

[0032] The features and advantages of the present invention can be further understood through the following detailed description. The examples provided are merely illustrative of the methods of the present invention and are not intended to limit the remainder of the present invention in any way.

[0033] The mass percentages of the components in the following examples are shown in Table 1.

[0034] Table 1 Mass percentage of each component in low-temperature silver paste of Examples 1-4 and Comparative Example 1

[0035]

[0036]

[0037] Example 1

[0038] A method for preparing low-temperature silver paste for easy-to-weld solar cells of the present invention comprises the following steps:

[0039] S1. Prepare modified dendritic silver powder and modified nano-spherical silver powder. Add excess polypropylene glycol and ethanol mixed solution to the two silver powders respectively, the mass ratio of polypropylene glycol to ethanol is 1:1, set the stirring speed to 100r / min, stir for 5h, filter and dry to obtain modified dendritic silver powder and modified nano-spherical silver powder. The particle size distribution D50 of the modified dendritic silver powder is 2.3μm, the tap density is 4.1g / mL, and the particle size distribution D50 of the modified nano-spherical silver powder is 486nm, and the tap density is 7.5g / mL.

[0040] S2. Prepare a polymer resin carrier. Take bisphenol A epoxy resin and add it to DBE, stir it in a water bath at a constant temperature of 60°C at a speed of 500 r / min until the epoxy resin is completely dissolved, and filter out impurities with a 400-mesh gauze to obtain a low-viscosity resin carrier.

[0041] S3. Mix a low-viscosity resin carrier, polyester resin, diethylene glycol butyl ether and a silane coupling agent, and disperse them in a centrifugal disperser at a speed of 1000 r / min for 1 min to obtain a mixed carrier A.

[0042] S4. Mix the mixed carrier A and the isocyanate curing agent, stir at a low speed of 200 r / min, and control the temperature to less than 20° C. to obtain a mixed carrier B.

[0043] S5. Add modified dendritic silver powder and nano-spherical silver powder to the mixed carrier B in 5 batches, with the mass ratio of modified dendritic silver powder to modified nano-spherical silver powder being 2:1. Stir while adding at a speed of 200 r / min and control the temperature to be less than 20°C to obtain a preliminarily dispersed slurry.

[0044] S6. The preliminarily dispersed slurry is put into a three-roll mill and rolled for 6 times to obtain a conductive silver paste with a fineness of less than 8 μm and a viscosity of 60-100 Pa·s.

[0045] Example 2

[0046] A method for preparing low-temperature silver paste for easy-to-weld solar cells of the present invention comprises the following steps:

[0047] S1. Prepare modified dendritic silver powder and modified nano-spherical silver powder. Add excess polypropylene glycol and ethanol mixed solution to the two silver powders respectively, the mass ratio of polypropylene glycol to ethanol is 1:3, set the stirring speed to 200r / min, stir for 3h, filter and dry to obtain modified dendritic silver powder and modified nano-spherical silver powder. The particle size distribution D50 of the modified dendritic silver powder is 3.5μm, the tap density is 5.0g / mL, and the particle size distribution D50 of the modified nano-spherical silver powder is 327nm, and the tap density is 4.4g / mL.

[0048] S2. Prepare a polymer resin carrier. Take an acrylic modified epoxy resin and add it to DBE, stir it in a water bath at 70°C at a constant temperature of 300 r / min until the epoxy resin is completely dissolved, and filter out impurities with a 400-mesh gauze to obtain a low-viscosity resin carrier.

[0049] S3. Mix a low-viscosity resin carrier, a polyurethane resin, diethylene glycol butyl ether, and a silane coupling agent, and disperse them in a centrifugal disperser at a speed of 1000 r / min for 1 min to obtain a mixed carrier A.

[0050] S4. Mix the mixed carrier A with the modified amine latent curing agent T31, stir at a low speed of 200 r / min, and control the temperature to <20° C. to obtain a mixed carrier B.

[0051] S5. Add modified dendritic silver powder and nano-spherical silver powder to the mixed carrier B in 5 batches, with the mass ratio of modified dendritic silver powder to modified nano-spherical silver powder being 11:1. Stir while adding at a speed of 200 r / min and control the temperature to <20°C to obtain a preliminarily dispersed slurry.

[0052] S6. The preliminarily dispersed slurry is put into a three-roll mill and rolled for 6 times to obtain a conductive silver paste with a fineness of less than 8 μm and a viscosity of 60-100 Pa·s.

[0053] Example 3

[0054] A method for preparing low-temperature silver paste for easy-to-weld solar cells of the present invention comprises the following steps:

[0055] S1. Prepare modified dendritic silver powder and modified nano-spherical silver powder. Add excess polypropylene glycol and ethanol mixed solution to the two silver powders respectively, the mass ratio of polypropylene glycol to ethanol is equal to 1:2, set the stirring speed to 200r / min, stir for 3h, filter and dry to obtain modified dendritic silver powder and modified nano-spherical silver powder. The particle size distribution D50 of the modified dendritic silver powder is 4.6μm, the tap density is 6.7g / mL, and the particle size distribution D50 of the modified nano-spherical silver powder is 230nm, and the tap density is 3.2g / mL.

[0056] S2. Prepare a polymer resin carrier. Take an acrylic modified epoxy resin and add it to DBE, stir it in a water bath at 70°C at a constant temperature of 300 r / min until the epoxy resin is completely dissolved, and filter out impurities with a 400-mesh gauze to obtain a low-viscosity resin carrier.

[0057] S3. Mix a low-viscosity resin carrier, a polyurethane resin, dimethyl adipate and a silane coupling agent, and disperse them in a centrifugal disperser at a speed of 1000 r / min for 1 min to obtain a mixed carrier A.

[0058] S4. Mix the mixed carrier A with the modified amine latent curing agent T31, stir at a low speed of 200 r / min, and control the temperature to <20° C. to obtain a mixed carrier B.

[0059] S5. Add modified dendritic silver powder and nano-spherical silver powder to the mixed carrier B in 5 batches, with the mass ratio of modified dendritic silver powder to modified nano-spherical silver powder being 16:1. Stir while adding at a speed of 200 r / min and control the temperature to be less than 20°C to obtain a preliminarily dispersed slurry.

[0060] S6. The preliminarily dispersed slurry is put into a three-roll mill and rolled for 6 times to obtain a conductive silver paste with a fineness of less than 8 μm and a viscosity of 60-100 Pa·s.

[0061] Example 4

[0062] A method for preparing low-temperature silver paste for easy-to-weld solar cells of the present invention comprises the following steps:

[0063] S1. Prepare modified dendritic silver powder and modified nano-spherical silver powder. Add excess polypropylene glycol and ethanol mixed solution to the two silver powders respectively, the mass ratio of polypropylene glycol to ethanol is equal to 3:1, set the stirring speed to 200r / min, stir for 6h, filter and dry to obtain modified dendritic silver powder and modified nano-spherical silver powder. The particle size distribution D50 of the modified dendritic silver powder is 2.9μm, the tap density is 5.3g / mL, and the particle size distribution D50 of the modified nano-spherical silver powder is 436nm, and the tap density is 5.8g / mL.

[0064] S2. Prepare a polymer resin carrier. Take bisphenol F epoxy resin and add it to DBE, stir it in a water bath at 80°C at a constant temperature of 400 r / min until the epoxy resin is completely dissolved, and then filter out impurities with a 400-mesh gauze to obtain a low-viscosity resin carrier.

[0065] S3. Mix a low-viscosity resin carrier, acrylic resin, diethylene glycol butyl ether acetate, and a silane coupling agent, and disperse them in a centrifugal disperser at a speed of 900 r / min for 2 min to obtain a mixed carrier A.

[0066] S4. Mix the mixed carrier A with the 2-ethyl-4-methylimidazole curing agent, stir at a low speed of 100 r / min, and control the temperature to be less than 20° C. to obtain a mixed carrier B.

[0067] S5. Add modified dendritic silver powder and nano-spherical silver powder to the mixed carrier B in 5 batches, with the mass ratio of modified dendritic silver powder to modified nano-spherical silver powder being 6:1. Stir while adding at a speed of 100 r / min and control the temperature to <20°C to obtain a preliminarily dispersed slurry.

[0068] S6. The preliminarily dispersed slurry is put into a three-roll mill and rolled for 6 times to obtain a conductive silver paste with a fineness of less than 8 μm and a viscosity of 60-100 Pa·s.

[0069] Comparative Example 1

[0070] A method for preparing low-temperature silver paste for solar cells comprises the following steps:

[0071] Preparation of polymer resin carrier: Bisphenol A epoxy resin was added to DBE, and stirred in a water bath at 60°C at a constant temperature of 500 r / min until the epoxy resin was completely dissolved, and then impurities were filtered out with a 400-mesh gauze to obtain a low-viscosity resin carrier.

[0072] A low-viscosity resin carrier, polyester resin, diethylene glycol butyl ether and a silane coupling agent were mixed and placed in a centrifugal disperser for dispersion at a speed of 1000 r / min for 1 min to obtain a mixed carrier A.

[0073] The mixed carrier A is mixed with the isocyanate curing agent, stirred at a low speed of 200 r / min, and the temperature is controlled at <20° C. to obtain a mixed carrier B.

[0074] Dendritic silver powder (unmodified) and nano-spherical silver powder (unmodified) were added to mixed carrier B in 5 batches, with a mass ratio of dendritic silver powder to nano-spherical silver powder of 2:1, and stirred while adding at a stirring speed of 200r / min, and the temperature was controlled at <20°C to obtain a preliminarily dispersed slurry. The particle size distribution D50 of the dendritic silver powder was 2.3μm, and the tap density was 4.1g / mL. The particle size distribution D50 of the nano-spherical silver powder was 481nm, and the tap density was 7.4g / mL.

[0075] The preliminarily dispersed slurry was put into a three-roll mill and rolled for 6 times to obtain a conductive silver paste with a fineness of less than 8 μm and a viscosity of 60-100 Pa·s.

[0076] The welding tensile performance test was performed on the above-mentioned Examples 1-4 and Comparative Example 1, and the test method was as follows:

[0077] Soak the solder strip in the flux for 1 minute and set the soldering iron temperature to 240°C;

[0078] Silver paste is used to print line patterns on the surface of ITO silicon wafers using screen printing;

[0079] Take out the soldering ribbon and align it with the line;

[0080] Use a soldering iron to dip a small amount of solder and push it along the solder ribbon to solder the solder ribbon onto the silver paste;

[0081] Bend the excess welding strip, fix it on the handheld tensile testing machine, reset the instrument data to zero, and pull it at a constant speed, reading the test peak data after each pull;

[0082] The maximum and minimum values ​​of a series of data are removed, and the remaining data are averaged to obtain welding tensile test data. The welding tensile performance test results of the low-temperature silver paste prepared in Examples 1-4 and Comparative Example 1 are shown in Table 2.

[0083] Table 2

[0084]

[0085]

[0086] From the test data in Table 2, it can be seen that the silver paste prepared in Examples 1-4 of the present invention by modifying the silver powder with polypropylene glycol has a higher welding tensile force, with an average welding tensile force of 1.4N; while the silver paste prepared in Comparative Example 1 using silver powder that has not been modified with polypropylene glycol has a welding tensile force of less than 1N, and the welding ribbon is easy to fall off; therefore, compared with the prior art, the preparation method of the silver paste provided by the present invention can effectively improve the welding tensile force, and the quality and service life of the battery can be greatly improved by using the silver paste in the HIT battery.

Claims

1. A method for preparing low-temperature silver paste for easy-to-weld solar cells, characterized in that: The easy-to-weld solar cell low-temperature silver paste comprises the following components, measured in percentage by mass: Silver powder 85%-92%, Resin 3%-8%, Organic solvent 3%-8%, Curing agent 0.2%-1.5%, Dispersant 0.2%-1%, Adhesion promoter 0.5%-2%; The silver powder is a mixture of modified dendritic silver powder and modified nano-spherical silver powder, wherein the mass ratio of the modified dendritic silver powder to the modified nano-spherical silver powder is (2-16):1; The modified dendritic silver powder is polyglycerol-modified dendritic silver powder, and the modified nano-spherical silver powder is polyglycerol-modified nano-spherical silver powder; The modified dendritic silver powder has a particle size distribution D50 of 2.0-5.0 μm and a tap density of 4-7 g / mL; The modified nano-spherical silver powder has a particle size distribution D50 of 200-500 nm and a tap density of 3-8 g / mL; The modified dendritic silver powder and modified nano-spherical silver powder are prepared by the following method: adding the dendritic silver powder and the nano-spherical silver powder to a mixed solution of excess polypropylene glycol and ethanol, respectively, controlling the mass ratio of polypropylene glycol to ethanol to be equal to 3: (1-9), setting the stirring speed to 100-200 r / min, stirring for 3-7 hours, filtering and drying to obtain the modified dendritic silver powder and the modified nano-spherical silver powder; The method for preparing the low-temperature silver paste for easy-to-weld solar cells comprises the following steps: S1, adding dendritic silver powder to a mixed solution of polypropylene glycol and ethanol, stirring, filtering and drying to obtain modified dendritic silver powder; adding nano-spherical silver powder to a mixed solution of polypropylene glycol and ethanol, stirring, filtering and drying to obtain modified nano-spherical silver powder; S2, taking a resin, an organic solvent, a dispersant, and an adhesion promoter, mixing them, putting them into a centrifugal disperser for dispersion, and obtaining a mixed carrier A; S3, mixing the mixed carrier A with the curing agent, stirring at a low speed to obtain a mixed carrier B; S4, adding the modified dendritic silver powder and the modified nano-spherical silver powder to the mixed carrier B in batches, stirring while adding, to obtain a preliminarily dispersed slurry; S5, rolling the preliminarily dispersed slurry for multiple times to obtain a low-temperature silver paste for solar cells that is easy to weld.

2. The method for preparing the low-temperature silver paste for easy-to-weld solar cells according to claim 1, characterized in that: The resin includes a main resin and an auxiliary resin. The main resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and acrylic modified epoxy resin. The auxiliary resin includes one or more of polyester resin, polyurethane resin, and acrylic resin.

3. The method for preparing the low-temperature silver paste for easy-to-weld solar cells according to claim 1, characterized in that: The organic solvent includes one or more of dibasic acid esters, diethylene glycol ethyl ether, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and dimethyl adipate.

4. The method for preparing the low-temperature silver paste for easy-to-weld solar cells according to claim 1, characterized in that: The curing agent includes one or more of isocyanate, imidazole and modified amine.

5. The method for preparing the low-temperature silver paste for easy-to-weld solar cells according to claim 1, characterized in that: The dispersant includes one or more of polyester and polyurethane, and the adhesion promoter includes a silane coupling agent.

6. The method for preparing the low-temperature silver paste for easy-to-weld solar cells according to claim 1, characterized in that: The step S2 specifically includes the following operations: adding the main resin in the resin to the solvent, stirring at a constant temperature of 60-80°C in a water bath at a stirring speed of 300-500r / min, until the main resin is completely dissolved, filtering impurities to obtain a low-viscosity resin carrier; taking the low-viscosity resin carrier, the remaining auxiliary resin in the resin, the organic solvent, the dispersant, and the adhesion promoter, mixing, and putting into a centrifugal disperser for dispersion at a speed of 800-1000r / min for 1-3min to obtain a mixed carrier A; In the steps S4 and S5, the temperature is controlled to be less than 20° C. during stirring.

Citation Information

Patent Citations

  • Silver paste with high conductivity at 80 DEG C and preparation method thereof

    CN111508637A

  • HJT battery low-temperature curing silver paste for fine printing and preparation method thereof

    CN113345623A

  • Preparation method of nano silver powder-containing low-temperature conductive silver paste for solar cell

    CN114464371A